Pancreatic Pseudocyst with Fistula to the Common Bile Duct Resolved by Combined Biliary and Pancreatic Stenting – A Case Report and Literature Review. (2009) - Ali, Jaber A Al; Chung, Henry; Munk, Peter L; Byrne, Michael F
Abstract : Pancreatic pseudocysts develop in 10% to 20% of patients with chronic pancreatitis, and can cause a variety of complications such as infection, bleeding or development of fistulae. However, fistulous communication with the common bile duct is very rare. The present report describes an unusual case of a patient with a large, symptomatic pancreatic pseudocyst with a fistula to the common bile duct that was treated successfully by combined biliary and pancreatic stenting.